Răspunsuri

2014-06-20T22:36:45+03:00
T (a, 2a +4) apartine Gf==> f(a)= 2a+4
                                         f(a)=3a-2 ==> 2a+4=3a-2
                                                              2a-3a=-4-2
                                                              -a=-6 ==> a=6 ==> T( 6, 16)
                                                                              2x6+4=12+4=16
Cel mai inteligent răspuns!
2014-06-20T22:37:22+03:00
T(a;2a+4)∈Gf   ⇒f(a)=2a+4
                               f(a)=3a-2

2a+4=3a-2

2a-3a=-2-4

-a=-6
a=6